Originally Posted by
wik_chick88 this is what i have:
\frac{1}{P(20000-P)} = \frac{A}{P} + \frac{B}{20000-P} (i brought the 200000 out the front of the integral)
= \frac{20000A - AP + BP}{P(20000-P)}
= \frac{20000A + (B-A)P}{20000-P}
equate coefficients:
20000A = 1, therefore A = \frac{1}{20000}
B - A = 0, therefore B = A = \frac{1}{20000}
therefore:
\frac{1}{P(20000-P)} = \frac{1}{20000P} + \frac{1}{20000(20000-P)}
have i gotten it right so far? i know where to go from here, as long as i havent made any mistakes!!